SERVICE QUALITY OF NURSE IN THE SCOPE OF NATIONAL HEALTH INSURANCE IN BATU CITY - Sih Ageng Lumadi; Pipin Shintya Wulandari (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. The Program of Indonesian Government in 2014 is to apply health insurance based program which known as National Health Insurance (NHI). The concept of this program is all of Indonesian will have health insurance based on Gotong Royong principal. The concept of health provider will be totally changes in health provider, referral system and financing. This study aimed to known the phenomena of nursing quality assurance under NHI which held in the first and the second grade of health provider in Batu, East Java. Method. Qualitative study with in depth interview was used to explore the phenomena. 18 participants were participating in this study taken based on the inclusion criteria were taken by purposive sampling. There were five theme which were nurse responsiveness, assurance of health provider, tangible, empathy and reliability. Result. The satisfaction of patients receive care in Batu BPJS still not achieved optimally. Discussion. It is suggests for the next researcher to explore the factors which barrier the nurse to give the optimal serveto national health insurance patient.Keywords: Service Quality, Nursing, NHI